Toward a Decentralized Cloud Storage and Internet Service Network: Challenges and Future Directions - Whitaker, Carsten; Laurent, Adele; Patel, Arvind (Journal of Computer Science and Software Applications, 2025)
The reliance on large corporations for high-performance and reliable cloud services presents vulnerabilities related to data security, privacy, and infrastructure failure. Decentralized networks offer a promising alternative by distributing resources and computational power across participants, mitigating dependence on centralized authorities. This paper investigates the development of a decentralized network for cloud storage and internet services, discussing key methods such as file encryption, distributed hash tables, and blockchain-based protocols. Although current solutions provide foundational progress, further research is needed to refine data structures, integrate Proof of Spacetime mechanisms, address potential attacks, and enhance fault tolerance and self-recovery. Additionally, the potential for transforming decentralized storage networks into a permanent, immutable web is highlighted, with future work proposed to address DNS resolution and robust file-sharing solutions for web integration.